If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 4 * 8 = 40 Multiply 4 * 8 n + 32 = 40 Reorder the terms: 32 + n = 40 Solving 32 + n = 40 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + n = 40 + -32 Combine like terms: 32 + -32 = 0 0 + n = 40 + -32 n = 40 + -32 Combine like terms: 40 + -32 = 8 n = 8 Simplifying n = 8
| (n-8)*4=20 | | 3x=13x-82 | | 5*n=24 | | 3ln(6x)=6 | | n*5=65 | | x^4+2=29 | | -11(t-3)-(t+7)=9 | | 5*4x=35 | | n+5=45 | | n+33=44 | | n+7=17 | | (n+2)*8=32 | | (n-3)*5=30 | | 6x^3-216= | | B^2+7b=44 | | a+0.03a=b | | a+0.3a=b | | a+0.1a=b | | -8x^4= | | x^2+3=6 | | 0.20(14000)+0.14t=0.18(14000+t) | | 3x+16=2x+10 | | 4a-8=8 | | 0.08x+0.12(260-x)=0.48x | | 0.05x+0.10(200-x)=0.45x | | 0.09k+0.13(k+300)=61 | | (5r-3)(6r+5)= | | (x-10)(x+10)= | | 9s+3=54 | | 14x^2+3-[4(x^2-4)+8]= | | 11x-13=2x+14 | | 4(3y-7)-(5y+3)= |